ʺThe state of development of teachers' social competence for work with learners in difficult life circumstances in the postgraduate education systemʺ - Dvornyk, O.; Ruban, N. (Problems of Engineer-Pedagogical Education, 2024)
The article is dedicated to analyzing the state of development of teachers' social competence for work with learners in difficult life circumstances in the postgraduate education system. The discourse focuses on putting forward the requirements of modern society for the development of social and professional competencies of educators. The important role of the postgraduate education system in ensuring the development of teachers' social competence has been noted. The analysis of the scientific literature revealed that the approach to developing teachers' social competence in the postgraduate education system remains under-researched and doesn't receive appropriate attention from scholars. The article notes that teachers' social competence is acquired through personal experience. Therefore, the focus is placed on the necessity of systematic development of this competence in the process of postgraduate education. An analysis of the current professional development programs for teachers regarding the development of their social competence for working with learners in difficult life circumstances has been presented. The material provides substantive content of the existing webinars and professional development courses that contribute to the development of teachers' social competence for working with learners in difficult life circumstances. It is noted that all the presented professional development programs for educators, which contribute to the development of teachers' social competence for working with learners in difficult life circumstances, have been developed at a quite high level. It has been established that the analyzed professional development courses for teachers focus only on certain aspects that may contribute to the difficult life circumstances of learners. It has been established that the analyzed professional development courses for teachers focus only on certain aspects that can lead to the difficult life circumstances in learners. It is determined that the considered professional development courses do not ensure the full-fledged development of teachers' social competence for working with learners in difficult life circumstances. As a result of the analysis of scientific research on the development of teachers' social competence for working with learners in difficult life circumstances, the necessity of improving and conducting a more detailed study of the mechanisms of this competence development has been substantiated.